Nascent RNA and the Coordination of Splicing with Transcription - Neugebauer, Karla M. (Cold Spring Harb Perspect Biol, 2019)
At each active protein-encoding gene, nascent RNA is tethered to the DNA axis by elongating RNA polymerase II (Pol II) and is continuously altered by splicing and other processing events during its synthesis. This review discusses the development of three major methods that enable us to track the conversion of precursor messenger RNA (pre-mRNA) to messenger RNA (mRNA) products in vivo: live-cell imaging, metabolic labeling of RNA, and RNA-seq of purified nascent RNA. These approaches are complementary, addressing distinct issues of transcription rates and intron lifetimes alongside spatial information regarding the gene position of Pol II at which spliceosomes act. The findings will be placed in the context of active transcription units, each of which—because of the presence of nascent RNA, Pol II, and features of the chromatin environment—will recruit a potentially gene-specific constellation of RNA binding proteins and processing machineries.